MENINGKATKAN KETERAMPILAN BERBICARA BAHASA ARAB MELALUI PERMAINAN BAHASA ISYRUNA SUALAN - Aisyatul Hanun; Herizal Herizal (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2020)
The purpose of this research is to knowing the application of the game isyruna sualan in enhancing language skills of speaks Arabic for students class VIIA MTsN 12 Banyuwangi 2018/2019 academic year. The fundamental problem is the low students on his willingness to learn arabic.The approach of this study used research a class action.The subject of this research are students and teachers of arabic language in class VIIA MTsN 12 banyuwangi. The data that used in this research are picture , lesson plans , syllabus ,result of the lessons and records of interviews. Data collection techniques with observation, , interview , documentation and also tests.The procedure of this study using models from kurt lewin, has to encompass, planning the act of, , observation and the reflections.The results found was the enhancing “hiwar” lessons with matter “baiti” use games language “isyruna sualan” after through two cycle with the details of the improvement of 76,41 % be 78,43 %. work completed.